CDK5 in oncology: recent advances and future prospects. (October 2017) - Lenjisa, Jimma Likisa; Tadesse, Solomon; Khair, Nishat Zareen; Kumarasiri, Malika; Yu, Mingfeng; Albrecht, Hugo; Milne, Robert; Wang, Shudong
Selective abrogation of cyclin-dependent kinases (CDK) activity is a highly promising strategy in cancer treatment. The atypical CDK, CDK5 has long been known for its role in neurodegenerative diseases, and is becoming an attractive drug target for cancer therapy. Myriads of recent studies have uncovered that aberrant expression of CDK5 contributes to the oncogenic initiation and progression of multiple solid and hematological malignancies. CDK5 is also implicated in the regulation of cancer stem cell biology. In this review, we present the current state of knowledge of CDK5 as a druggable target for cancer treatment. We also provide a detailed outlook of designing selective and potent inhibitors of this enzyme.